If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4 + -1b) = 3(2b + 2) (4 * 4 + -1b * 4) = 3(2b + 2) (16 + -4b) = 3(2b + 2) Reorder the terms: 16 + -4b = 3(2 + 2b) 16 + -4b = (2 * 3 + 2b * 3) 16 + -4b = (6 + 6b) Solving 16 + -4b = 6 + 6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6b' to each side of the equation. 16 + -4b + -6b = 6 + 6b + -6b Combine like terms: -4b + -6b = -10b 16 + -10b = 6 + 6b + -6b Combine like terms: 6b + -6b = 0 16 + -10b = 6 + 0 16 + -10b = 6 Add '-16' to each side of the equation. 16 + -16 + -10b = 6 + -16 Combine like terms: 16 + -16 = 0 0 + -10b = 6 + -16 -10b = 6 + -16 Combine like terms: 6 + -16 = -10 -10b = -10 Divide each side by '-10'. b = 1 Simplifying b = 1
| lnx+lnx+2=6 | | (-6v+4)(-4v+2)=0 | | x+52/x=17 | | 1x+-8=-2 | | 16xy+11y=0 | | 5s-4s=45 | | x+7/x=(6x+14)/7 | | 0.66p+12=0.33p+10 | | -10x=-29 | | x+7/x=6x+14/7 | | (-6n+2)(5n+3)=0 | | (5+b)/2=-11 | | -k/5=12 | | 3/(x-9)=5/(x-6) | | 3x+-2=-11 | | 3x+10=110 | | (3+a)1/2=5 | | 14.37x-1.1245+5.687=978.654 | | 3/x-9=5/x-6 | | x-3pi=5pi | | 2(x-4)=5(x-7) | | -3(x-5)=2x+6 | | 6(x-1)=3x+6 | | 5(x+2)-2=6x-9 | | (2x+7)(x+1)=0 | | 100-3x=5x-28 | | (3+a)/2=5 | | 7-2(x-3)=12-5x | | 2y^2-y=-10 | | x/x+1-4/x-2 | | 6(5x*12)=162 | | x=7+-2+2y |